FAKTOR BAURAN PEMASARAM YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI RUMAH MAKAN MAK KARI PANAM PEKANBARU - Rifka Putri Dwineti; Almasdi Syahza; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: This study aims to determine what marketing mix factors considered by consumers in making purchasing decisions shopped at the restaurant Mak Kari Panam Pekanbaru. The population in this study are all consumers who shop at the restaurant mak kari. In determining the number of samples, researchers used a purposive sampling method, the sample size used as respondents in this study were 100 respondents. Data were analyzed using multiple linear regression analysis, t test and F test with a significance level of 0.05%. Based on the survey results revealed that all the free variable pricing, product, location and promotion significantly influence purchasing decisions with significant value 0.000 <0.05. Price, product, location and promotion are the factors that influence purchasing decisions are categorized marketing mix. Large Marketing mix factors influence the purchasing decision amounted to 66.3%, the remaining 33.7% influenced by other factors not examined in this study such as service and motivation. And from all four factors of the marketing mix variables (price, product, place / location and promotion) is more dominant influential factor that is influenced by factors promotion by 25.7%Key Word : Marketing Mix, Purchase Decision